Mengungkapkan Keistimewaan Surah Makiyyah dan Madaniyah - Rumza Amalia; Salsabil Nur Shilfiya Khildan; Mohammad Salik (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Makkiyah and Madaniyah are foundational concepts in Ulumul Qur'an that classify Qur'anic verses and chapters based on the period of revelation, whether before or after the Prophet Muhammad's migration (Hijrah) to Medina. This study is significant because it provides insight into the historical context, linguistic style, and thematic content of Qur'anic verses. This article aims to explain the definition and characteristics of Makkiyah and Madaniyah, the methodological bases for their classification, the grouping of surahs, and their utility in Qur'anic interpretation. This research employs a library research method (studi kepustakaan) by collecting and critically analyzing various primary and secondary literary sources related to Qur'anic sciences. The results reveal that Makkiyah verses predominantly contain themes of creed (aqidah), monotheism (tawhid), morality, and eschatology, delivered in a concise, powerful, and rhetorical language. In contrast, Madaniyah verses focus more on Islamic law (syariat), social affairs, politics, and community life, characterized by a longer and more systematic linguistic style. This classification aids scholars in understanding the Islamic legal system methodically, analyzing the relationship between abrogating (nasikh) and abrogated (mansukh) verses, and provides a more precise understanding of the context of revelation. The study of Makkiyah and Madaniyah is crucial for a comprehensive, historical, and contextual understanding of the Qur'an.